Sustainability Action Evidence From Indonesia: How Can Carbon Trading and Esg Disclosure Affect Firm Value? - Arif Nugroho; La Ode Sabaruddin (Universitas Muhammadiyah Malang, 2025)
Purpose: This study aims to empirically examine the effect of carbon trading and environmental, social, and governance (ESG) disclosure on firm value. Methodology/approach: This study uses quantitative approach and secondary data from manufacturing companies listed on the IDX for the period 2022-2023. Data was collected from annual reports and sustainability reports. Data was analyzed multiple regression analysis techniques. Findings: The results indicate Carbon Trading has a negative impact on firm value, while Environmental, Social, and Governance (ESG) disclosure has a positive impact on firm value. Practical implications: Companies should strengthen and pay more attention to carbon trading to meet the needs of stakeholders and maintain ESG disclosure for long-term investor sustainability. Investors should also give greater consideration to financial and non-financial information when assessing companies for decision-making purposes. Originality/value: This study builds upon previous research examining the impact of Carbon Trading in China. It also introduces the variable of Environmental, Social, and Governance (ESG) disclosure on firm value. This study was conducted on manufacturing companies that were previously in the energy sector and tested the implementation of Carbon Trading in Indonesia with regulations that were established in 2022 and enacted in 2023.